Nano-cellulose-based flexible transparent electrode for thin film heater and preparation method and application of nano-cellulose-based flexible transparent electrode
Through the method of combining interface customization strategy with ultraviolet induced plasma welding, TCNF/AgNW composite electrodes were prepared, which solved the problems of high contact resistance and low interface adhesion of AgNWs flexible transparent electrodes, and achieved high-performance and stable flexible transparent electrodes, which were suitable for thin film heaters and other applications.
Patent Information
- Application Number
- CN202411744551.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-01
- Publication Date
- 2025-03-04
AI Technical Summary
The existing flexible transparent electrodes based on AgNWs have poor mechanical stability and performance due to high contact resistance and low interface adhesion, and traditional welding technology has problems such as high power consumption, safety hazards and environmental pollution.
The TCNF/AgNW composite electrode was prepared by combining interface customization strategies with ultraviolet induced plasma welding. The stability of the interface crosslinking and conductive network is enhanced by polydopamine grafting and N,N-bis(acryloyl)cysteamine as surface adsorbent.
It achieves low contact resistance, high light transmittance and excellent stability and durability. It is suitable for applications such as thin film heaters and has the advantages of low driving voltage, high saturation temperature and fast response.
Smart Images

Figure CN119560231A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of cellulose-based conductive film materials, and in particular relates to a nanocellulose-based flexible transparent electrode for a film heater, and a preparation method and application thereof. Background Art
[0002] Flexible transparent conductive electrodes (FTCEs), as an important component of flexible electronics, have promoted the advancement of a series of flexible electronic devices such as flexible displays, smart wearable devices and thin film heaters. Although commercial materials such as indium tin oxide (ITO) exhibit excellent optoelectronic properties, their inherent brittleness, high cost and scarcity of indium limit their applicability to the next generation of flexible electronic devices. To overcome these limitations, metal nanowires have been explored for the construction of high-performance FTCEs. Among them, silver nanowires (AgNWs) have become a promising alternative due to their excellent optoelectronic properties, compatibility with flexible substrates and potential for large-scale production. However, flexible transparent electrodes based on AgNWs are usually limited by high contact resistance; secondly, the relatively low surface activity of AgNWs weakens the interfacial adhesion with the flexible substrate, resulting in severe delamination and reduced mechanical stability.
[0003] Many welding techniques have been proposed to reduce contact resistance, including thermal annealing, chemical treatment, solvent induction, mechanical pressing, and photoplasma welding. However, each method has certain limitations. For example, thermal annealing challenges the heat resistance of the substrate; chemical treatment and solvent induced welding require strict control of the reaction time and may cause environmental pollution; high pressure during mechanical pressing can damage the electrode structure and active layer. Compared with other methods, photoplasma welding is valued for its simplicity, cost-effectiveness, and non-contact processing. Despite these advantages, high power consumption, potential safety issues, and long exposure time have posed obstacles to the commercial development of FTCEs.
[0004] To ensure mechanical stability, various flexible substrates such as polyethylene terephthalate (PET), polyimide (PI), polydimethylsiloxane (PDMS), polycarbonate (PC), and other non-renewable petroleum-based polymers have been used. However, their limited surface activity results in poor adhesion. As an alternative, 2,2',6',6'-tetramethylpiperidin-1-oxygenated cellulose nanofibers (TCNFs) have shown great potential as a flexible, transparent substrate material with eco-friendly properties, tunable optical properties, and abundant hydroxyl and carboxyl groups on their surface, which can enhance adhesion with AgNWs. Ensuring high interfacial adhesion between TCNFs and AgNWs is key to obtaining high-performance flexible electronics. Summary of the invention
[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a nanocellulose-based flexible transparent electrode.
[0006] Another object of the present invention is to provide a nanocellulose-based flexible transparent electrode prepared by the above preparation method.
[0007] This paper proposes a method that combines interface customization strategy with UV-induced plasma welding to prepare TCNF / AgNW composite electrodes. The resulting composite electrodes exhibit low contact resistance, high transmittance, and excellent stability and durability under various conditions.
[0008] Another object of the present invention is to provide application of the above-mentioned nanocellulose-based flexible transparent electrode in a thin film heater.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] In a first aspect, the present invention provides a method for preparing a nanocellulose-based flexible transparent electrode, comprising the following steps:
[0011] (1) Preparation of PDA-TCNF composite film: The dried TCNF membrane was soaked in a 50 wt% 3-aminopropyltriethoxysilane (APTES) ethanol solution. In order to remove the excess APTES, the APTES functionalized film (NH2-TCNF) was ultrasonically cleaned with water and ethanol. The NH2-TCNF membrane was immersed in a mixture of 200.0 mg DA·HCl and 100 ml Tris buffer (10 mM, pH 8.5) and stirred at room temperature for several hours. Subsequently, the treated NH2-TCNF membrane was rinsed with water several times to obtain a PDA-modified TCNF membrane (PDA-TCNF).
[0012] (2) Preparation of AgNW-S conductive network: The glass slide was cleaned with detergent, deionized water, acetone, and isopropanol. Subsequently, AgNWs dispersion (2 mg mL -1 ) was spin-coated on a glass slide. To eliminate the residual polyvinylpyrrolidone (PVP) sealant, the resulting conductive film was washed three times with deionized water and ethanol alternately. Next, the film was heated on a hot plate and then incubated in N,N-bis(acryloyl)cysteamine (BACA) / methanol solution (5 mg mL -1 Finally, the AgNW-S was rinsed with methanol to remove the excess BACA residue.
[0013] (3) Preparation of PDA-TCNF / AgNW-S composite electrode: First, the AgNW-S conductive film was transferred to the PDA-TCNF wet film. Then, hot pressing was performed to form a PDA-TCNF / AgNW-S composite electrode. The composite electrode after interface adjustment was named PDA-TCNF / AgNW-S composite electrode. The PDA-TCNF / AgNW-S composite electrode was exposed to ultraviolet light <400nm through a mask, and the light power density and irradiation time were adjusted. The electrode was named PDA-TCNF / AgNW-S / 3 composite electrode.
[0014] In step (1), the nanocellulose film preferably has a thickness of 0.2 to 0.3 mm, a diameter of 20 to 40 nm, and a length of 500 to 2000 nm.
[0015] In step (1), the dried TCNF membrane is preferably immersed in a 50 wt % 3-aminopropyltriethoxysilane (APTES) ethanol solution for 15 to 60 min.
[0016] Preferably, the ultrasonic cleaning time is 1 hour.
[0017] Preferably, the stirring time at room temperature is 1 to 4 hours.
[0018] In step (2), AgNWs dispersion (2 mg mL -1 ) is spin-coated on a glass slide at a spin coating speed of 800 to 1200 rpm, and the AgNW-S film is heated at 60 to 90° C. for 10 to 40 min.
[0019] Preferably, the N,N-bis(acryloyl)cysteamine (BACA) / methanol solution (5 mg mL -1 ) and soak for another 10 to 60 minutes.
[0020] The AgNW-S conductive film is transferred to the PDA-TCNF wet film as described in step (3). Subsequently, the film is hot pressed at 60-80°C for 6-12 hours. Under ultraviolet light of <400nm, the optical power density is 30-60mW cm -2 The irradiation time is 2 to 20 minutes respectively.
[0021] A nanocellulose-based flexible transparent electrode is prepared by the above preparation method.
[0022] Performance indicators of the nanocellulose-based flexible transparent electrode: Contact resistance: 7.26Ωsq -1 ~108.2Ωsq -1; Transmittance (550nm): 80%~91%; Quality factor (FoM): 33.7~324.2; Number of times of resisting tape adhesion: 10~350 times.
[0023] In a second aspect, the present invention provides a nanocellulose-based flexible transparent electrode prepared by the preparation method and applied to a thin film heater.
[0024] The film heater is manufactured by applying a silver paste brush on both ends of the composite electrode and using a conductive copper tape as a channel to connect a constant voltage DC power supply.
[0025] The voltage of the DC power supply of the film heater is 1-5V.
[0026] The saturation temperature range of the obtained thin film heater is between 32.1 and 133.7°C.
[0027] The nanocellulose-based flexible transparent electrode obtained by the present invention has high conductivity, high transparency, high interface adhesion, 91% light transmittance, and a contact resistance of 108.2Ωsq -1 , the number of times of resisting tape adhesion reaches 350 times. The saturation temperature range of the film heater is between 32.1 and 133.7℃.
[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0029] (1) The present invention is based on green and environmentally friendly nanocellulose materials, which are abundant in nature and have strong degradation ability. The transparent film prepared has unique optical properties. The nanocellulose-based flexible transparent electrode prepared by vacuum filtration, hot pressing and spin coating has strong operability and is suitable for large-scale production.
[0030] (2) The present invention adopts the method of grafting polydopamine onto the TCNF film to enhance the surface properties. N, N-di(acryloyl)cysteamine is used as a surface adsorbent for the AgNWs conductive network. The sulfur atoms in BACA form strong coordination with AgNWs, and the acrylamide groups at its ends promote interfacial crosslinking with PDA. This interface customization strategy can achieve strong crosslinking between the substrate and the conductive layer material.
[0031] (3) The present invention realizes the effect of low-intensity ultraviolet irradiation (60W cm) through interface customization strategy. -2 ) under the condition of rapid plasma welding of AgNWs, the obtained nanocellulose-based flexible transparent electrode has a high quality factor. In addition, the obtained nanocellulose-based flexible transparent electrode can be used in thin film heaters, with many advantages such as low driving voltage (5V), high saturation temperature (133.7℃), and fast response speed (<10s). BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The sheet resistance and transmittance at 550nm of the obtained AgNW, TCNF / AgNW, PDA-TCNF / AgNW and PDA-TCNF / AgNW-S composite electrodes.
[0033] Figure 2 are the FoM values of the obtained AgNW, TCNF / AgNW, PDA-TCNF / AgNW and PDA-TCNF / AgNW-S composite electrodes.
[0034] Figure 3 This is the UV-visible light transmission spectrum of the obtained PDA-TCNF / AgNW-S composite electrode before and after plasma welding.
[0035] Figure 4 Sheet resistance of the obtained AgNW, TCNF / AgNW and PDA-TCNF / AgNW-S composite electrodes before and after plasma welding.
[0036] Figure 5 is the FoM value of the obtained PDA-TCNF / AgNW-S and PDA-TCNF / AgNW-S / 3 composite electrodes.
[0037] Figure 6 The curves (R / R0) of the sheet resistance of the AgNW / PET, TCNF / AgNW, PDA-TCNF / AgNW-S and PDA-TCNF / AgNW-S / 3 composite electrodes obtained with the change of the tape test times are shown.
[0038] Figure 7 The surface temperature of the obtained PDA-TCNF / AgNW-S / 3 composite electrode applied to a thin film heater changes with time under different power supply voltages. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials and reagents used in the present invention can be obtained from commercial sources unless otherwise specified. For process parameters not specifically noted, conventional techniques can be used.
[0040] Example 1
[0041] In a first aspect, the present invention provides a method for preparing a nanocellulose-based flexible transparent electrode, comprising the following steps:
[0042] (1) Preparation of PDA-TCNF composite film: The dried TCNF membrane was soaked in a 50wt% 3-aminopropyltriethoxysilane (APTES) ethanol solution for 30min. In order to remove the excess APTES, the APTES functionalized film (NH2-TCNF) was ultrasonically cleaned with water and ethanol. The NH2-TCNF membrane was immersed in a mixture of 200.0mg DA·HCl and 100ml Tris buffer (10mM, pH 8.5) and stirred at room temperature for 2h. Subsequently, the treated NH2-TCNF membrane was rinsed with water several times to obtain the PDA-modified TCNF membrane (PDA-TCNF).
[0043] (2) Preparation of AgNW-S conductive network: The glass slide was cleaned with detergent, deionized water, acetone, and isopropanol. Subsequently, AgNWs dispersion (2 mg mL -1 ) was spin-coated on a glass slide. To eliminate the residual polyvinylpyrrolidone (PVP) sealant, the resulting conductive film was washed three times with deionized water and ethanol alternately. Next, the film was heated on a hot plate at 80 °C for 15 min and then in N,N-bis(acryloyl)cysteamine (BACA) / methanol solution (5 mg mL -1 ) for another 15 min. Finally, the AgNW-S was rinsed with methanol to remove the excess BACA residue.
[0044] (3) Preparation of PDA-TCNF / AgNW-S composite electrode: First, the AgNW-S conductive film was transferred to the PDA-TCNF wet film. Subsequently, the PDA-TCNF / AgNW-S composite electrode was formed by hot pressing at 70 °C for 8 h. The composite electrode after interface adjustment was named PDA-TCNF / AgNW-S composite electrode. The PDA-TCNF / AgNW-S composite electrode was exposed to ultraviolet light <400 nm through a mask with an optical power density of approximately 60 mW cm -2 , and the irradiation time was 12 min. The electrode was named PDA-TCNF / AgNW-S / 3 composite electrode.
[0045] A nanocellulose-based flexible transparent electrode is prepared by the above preparation method.
[0046] The performance indicators of the nanocellulose-based flexible transparent electrode are as follows: Figure 1-4 Shown: Contact resistance: 7.26Ωsq -1 ; Transmittance (550nm): 91%; Quality factor (FoM): 324.2; Number of times of resisting tape adhesion: 350 times.
[0047] In a second aspect, the present invention provides a nanocellulose-based flexible transparent electrode prepared by the preparation method and applied to a thin film heater.
[0048] The film heater is manufactured by applying a silver paste brush on both ends of the composite electrode and using a conductive copper tape as a channel to connect a constant voltage DC power supply.
[0049] The voltage of the DC power supply of the film heater is 5V.
[0050] The saturation temperature of the obtained film heater is as follows Figure 5 Shown is 133.7°C.
[0051] Example 2
[0052] In a first aspect, the present invention provides a method for preparing a nanocellulose-based flexible transparent electrode, comprising the following steps:
[0053] (1) Preparation of PDA-TCNF composite film: The dried TCNF membrane was soaked in 50wt% 3-aminopropyltriethoxysilane (APTES) ethanol solution for 15min. In order to remove the excess APTES, the APTES functionalized film (NH2-TCNF) was ultrasonically cleaned with water and ethanol. The NH2-TCNF membrane was immersed in a mixture of 200.0mg DA·HCl and 100ml Tris buffer (10mM, pH 8.5) and stirred at room temperature for 1h. Subsequently, the treated NH2-TCNF membrane was rinsed with water several times to obtain the PDA-modified TCNF membrane (PDA-TCNF).
[0054] (2) Preparation of AgNW-S conductive network: The glass slide was cleaned with detergent, deionized water, acetone, and isopropanol. Subsequently, AgNWs dispersion (2 mg mL -1 ) was spin-coated on a glass slide. To eliminate the residual polyvinylpyrrolidone (PVP) sealant, the resulting conductive film was washed three times with deionized water and ethanol alternately. Next, the film was heated on a hot plate at 60 °C for 30 min and then in N,N-bis(acryloyl)cysteamine (BACA) / methanol solution (5 mg mL -1 ) for another 10 min. Finally, the AgNW-S was rinsed with methanol to remove the excess BACA residue.
[0055] (3) Preparation of PDA-TCNF / AgNW-S composite electrode: First, the AgNW-S conductive film was transferred to the PDA-TCNF wet film. Subsequently, the PDA-TCNF / AgNW-S composite electrode was formed by hot pressing at 60 °C for 6 h. The composite electrode after interface adjustment was named PDA-TCNF / AgNW-S composite electrode. The PDA-TCNF / AgNW-S composite electrode was exposed to ultraviolet light <400 nm through a mask, and the light power density was about 30 mW cm -2 , and the irradiation time was 2 min. The electrode was named PDA-TCNF / AgNW-S / 3 composite electrode.
[0056] A nanocellulose-based flexible transparent electrode is prepared by the above preparation method.
[0057] The performance indicators of the nanocellulose-based flexible transparent electrode are as follows: Figure 1-4 Shown: Contact resistance: 10.21Ωsq -1 ; Transmittance (550nm): 88%; Quality factor (FoM): 279.7; Number of times of resisting tape adhesion: 150 times.
[0058] In a second aspect, the present invention provides a nanocellulose-based flexible transparent electrode prepared by the preparation method and applied to a thin film heater.
[0059] The film heater is manufactured by applying a silver paste brush on both ends of the composite electrode and using a conductive copper tape as a channel to connect a constant voltage DC power supply.
[0060] The voltage of the DC power supply of the film heater is 4V.
[0061] The saturation temperature of the obtained film heater is as follows Figure 5 Shown is 97.9°C.
[0062] Example 3
[0063] In a first aspect, the present invention provides a method for preparing a nanocellulose-based flexible transparent electrode, comprising the following steps:
[0064] (1) Preparation of PDA-TCNF composite film: The dried TCNF membrane was soaked in a 50wt% 3-aminopropyltriethoxysilane (APTES) ethanol solution for 45min. In order to remove the excess APTES, the APTES functionalized film (NH2-TCNF) was ultrasonically cleaned with water and ethanol. The NH2-TCNF membrane was immersed in a mixture of 200.0mg DA·HCl and 100ml Tris buffer (10mM, pH 8.5) and stirred at room temperature for 3h. Subsequently, the treated NH2-TCNF membrane was rinsed with water several times to obtain the PDA-modified TCNF membrane (PDA-TCNF).
[0065] (2) Preparation of AgNW-S conductive network: The glass slide was cleaned with detergent, deionized water, acetone, and isopropanol. Subsequently, AgNWs dispersion (2 mg mL -1 ) was spin-coated on a glass slide. To eliminate the residual polyvinylpyrrolidone (PVP) sealant, the resulting conductive film was washed three times with deionized water and ethanol alternately. Next, the film was heated on a hot plate at 80 °C for 40 min and then in N,N-bis(acryloyl)cysteamine (BACA) / methanol solution (5 mg mL -1 ) for another 40 min. Finally, the AgNW-S was rinsed with methanol to remove the excess BACA residues.
[0066] (3) Preparation of PDA-TCNF / AgNW-S composite electrode: First, the AgNW-S conductive film was transferred to the PDA-TCNF wet film. Subsequently, the PDA-TCNF / AgNW-S composite electrode was formed by hot pressing at 80 °C for 10 h. The composite electrode after interface adjustment was named PDA-TCNF / AgNW-S composite electrode. The PDA-TCNF / AgNW-S composite electrode was exposed to ultraviolet light <400 nm through a mask, and the optical power density was about 40 mW cm -2 , and the irradiation time was 6 min respectively. The electrode was named PDA-TCNF / AgNW-S / 3 composite electrode.
[0067] A nanocellulose-based flexible transparent electrode is prepared by the above preparation method.
[0068] The performance indicators of the nanocellulose-based flexible transparent electrode are as follows: Figure 1-4 Shown: Contact resistance: 9.41Ωsq -1 ; Transmittance (550nm): 85%; Quality factor (FoM): 236.6; Number of times of resisting tape adhesion: 260 times.
[0069] In a second aspect, the present invention provides a nanocellulose-based flexible transparent electrode prepared by the preparation method and applied to a thin film heater.
[0070] The film heater is manufactured by applying a silver paste brush on both ends of the composite electrode and using a conductive copper tape as a channel to connect a constant voltage DC power supply.
[0071] The voltage of the DC power supply of the film heater is 3V.
[0072] The saturation temperature of the obtained film heater is as follows Figure 5 Shown is 65.2°C.
[0073] Example 4
[0074] In a first aspect, the present invention provides a method for preparing a nanocellulose-based flexible transparent electrode, comprising the following steps:
[0075] (1) Preparation of PDA-TCNF composite film: The dried TCNF membrane was soaked in a 50wt% 3-aminopropyltriethoxysilane (APTES) ethanol solution for 60min. In order to remove the excess APTES, the APTES functionalized film (NH2-TCNF) was ultrasonically cleaned with water and ethanol. The NH2-TCNF membrane was immersed in a mixture of 200.0mg DA·HCl and 100ml Tris buffer (10mM, pH 8.5) and stirred at room temperature for 4h. Subsequently, the treated NH2-TCNF membrane was rinsed with water several times to obtain the PDA-modified TCNF membrane (PDA-TCNF).
[0076] (2) Preparation of AgNW-S conductive network: The glass slide was cleaned with detergent, deionized water, acetone, and isopropanol. Subsequently, AgNWs dispersion (2 mg mL -1 ) was spin-coated on a glass slide. To eliminate the residual polyvinylpyrrolidone (PVP) sealant, the resulting conductive film was washed three times with deionized water and ethanol alternately. Next, the film was heated on a hot plate at 90 °C for 40 min and then in N,N-bis(acryloyl)cysteamine (BACA) / methanol solution (5 mg mL -1 ) for another 60 min. Finally, the AgNW-S was rinsed with methanol to remove the excess BACA residues.
[0077] (3) Preparation of PDA-TCNF / AgNW-S composite electrode: First, the AgNW-S conductive film was transferred to the PDA-TCNF wet film. Subsequently, the PDA-TCNF / AgNW-S composite electrode was formed by hot pressing at 80 °C for 12 h. The composite electrode after interface adjustment was named PDA-TCNF / AgNW-S composite electrode. The PDA-TCNF / AgNW-S composite electrode was exposed to ultraviolet light <400 nm through a mask with an optical power density of approximately 50 mW cm -2 , and the irradiation time was 16 min. The electrode was named PDA-TCNF / AgNW-S / 3 composite electrode.
[0078] A nanocellulose-based flexible transparent electrode is prepared by the above preparation method.
[0079] The performance indicators of the nanocellulose-based flexible transparent electrode are as follows: Figure 1-4 Shown: Contact resistance: 8.32Ωsq -1 ; Transmittance (550nm): 81%; Quality factor (FoM): 203.9; Number of times of resisting tape adhesion: 290 times.
[0080] In a second aspect, the present invention provides a nanocellulose-based flexible transparent electrode prepared by the preparation method and applied to a thin film heater.
[0081] The film heater is manufactured by applying a silver paste brush on both ends of the composite electrode and using a conductive copper tape as a channel to connect a constant voltage DC power supply.
[0082] The voltage of the DC power supply of the film heater is 2V.
[0083] The saturation temperature of the obtained film heater is as follows Figure 5 Shown is 41.9°C.
[0084] Comparative Example 1
[0085] In a first aspect, the present invention provides a method for preparing a nanocellulose-based flexible transparent electrode, comprising the following steps:
[0086] (1) Preparation of TCNF composite film: The dried TCNF membrane was obtained by vacuum-assisted filtration.
[0087] (2) Preparation of AgNW conductive network: The glass slide was cleaned with detergent, deionized water, acetone, and isopropanol. Subsequently, AgNWs dispersion (2 mg mL -1) was spin-coated on a glass slide. To eliminate the residual polyvinylpyrrolidone (PVP) sealant, the resulting conductive film was washed three times with deionized water and ethanol alternately. Next, the film was heated on a hot plate at 80°C for 15 min.
[0088] (3) Preparation of TCNF / AgNW composite electrode: First, the AgNW conductive film was transferred to the TCNF wet film. Then, the TCNF / AgNW composite electrode was formed by hot pressing at 70 °C for 8 h. The TCNF / AgNW composite electrode was exposed to ultraviolet light <400 nm through a mask with a light power density of about 60 mW cm -2 , and the irradiation time was 12 min. The electrode was named TCNF / AgNW / 3 composite electrode.
[0089] A nanocellulose-based flexible transparent electrode is prepared by the above preparation method.
[0090] The performance indicators of the nanocellulose-based flexible transparent electrode are as follows: Figure 2 , 4, 6, 7 as shown: Contact resistance: 18.48Ωsq -1 ; Transmittance (550nm): 87%; Quality factor (FoM): 141.2; Number of times of resisting tape adhesion: 40 times.
[0091] In a second aspect, the present invention provides a nanocellulose-based flexible transparent electrode prepared by the preparation method and applied to a thin film heater.
[0092] The film heater is manufactured by applying a silver paste brush on both ends of the composite electrode and using a conductive copper tape as a channel to connect a constant voltage DC power supply.
[0093] The voltage of the DC power supply of the film heater is 5V.
[0094] The saturation temperature of the obtained thin film heater was 53.2°C.
[0095] Comparative Example 2
[0096] In a first aspect, the present invention provides a method for preparing a nanocellulose-based flexible transparent electrode, comprising the following steps:
[0097] (1) Preparation of PDA-TCNF composite film: The dried TCNF membrane was soaked in a 50wt% 3-aminopropyltriethoxysilane (APTES) ethanol solution for 30min. In order to remove the excess APTES, the APTES functionalized film (NH2-TCNF) was ultrasonically cleaned with water and ethanol. The NH2-TCNF membrane was immersed in a mixture of 200.0mg DA·HCl and 100ml Tris buffer (10mM, pH 8.5) and stirred at room temperature for 2h. Subsequently, the treated NH2-TCNF membrane was rinsed with water several times to obtain the PDA-modified TCNF membrane (PDA-TCNF).
[0098] (2) Preparation of AgNW-S conductive network: The glass slide was cleaned with detergent, deionized water, acetone, and isopropanol. Subsequently, AgNWs dispersion (2 mg mL -1 ) was spin-coated on a glass slide. To eliminate the residual polyvinylpyrrolidone (PVP) sealant, the resulting conductive film was washed three times with deionized water and ethanol alternately. Next, the film was heated on a hot plate at 80 °C for 15 min and then in N,N-bis(acryloyl)cysteamine (BACA) / methanol solution (5 mg mL -1 ) for another 15 min. Finally, the AgNW-S was rinsed with methanol to remove the excess BACA residue.
[0099] (3) Preparation of PDA-TCNF / AgNW-S composite electrode: First, the AgNW-S conductive film was transferred to the PDA-TCNF wet film. Subsequently, the PDA-TCNF / AgNW-S composite electrode was formed by hot pressing at 70°C for 8 h. The composite electrode after interface adjustment was named PDA-TCNF / AgNW-S composite electrode.
[0100] A nanocellulose-based flexible transparent electrode is prepared by the above preparation method.
[0101] The performance indicators of the nanocellulose-based flexible transparent electrode are as follows: Figure 2 , 4, 6, 7 as shown: Contact resistance: 26.26Ωsq -1 ; Transmittance (550nm): 84%; Quality factor (FoM): 78.8; Number of times of resisting tape adhesion: 320 times.
[0102] In a second aspect, the present invention provides a nanocellulose-based flexible transparent electrode prepared by the preparation method and applied to a thin film heater.
[0103] The film heater is manufactured by applying a silver paste brush on both ends of the composite electrode and using a conductive copper tape as a channel to connect a constant voltage DC power supply.
[0104] The voltage of the DC power supply of the film heater is 5V.
[0105] The saturation temperature of the obtained thin film heater was 43.3°C.
[0106] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a nanocellulose-based flexible transparent electrode, characterized in that: The following steps are involved: (1) Preparation of PDA-TCNF composite film: The dried TCNF membrane was soaked in a 50wt% 3-aminopropyltriethoxysilane (APTES) ethanol solution. In order to remove excess APTES, the APTES functionalized film (NH2-TCNF) was ultrasonically cleaned with water and ethanol. The NH2-TCNF membrane was immersed in a mixture of 200.0mg DA·HCl and 100ml Tris buffer (10mM, pH8.5) and stirred at room temperature for several hours. Subsequently, the treated NH2-TCNF membrane was rinsed with water several times to obtain a PDA-modified TCNF membrane (PDA-TCNF); (2) Preparation of AgNW-S conductive network: The glass slide was cleaned with detergent, deionized water, acetone, and isopropanol. Subsequently, AgNWs dispersion (2 mg mL -1 ) was spin-coated on a glass slide. To eliminate the residual polyvinylpyrrolidone (PVP) sealant, the resulting conductive film was washed three times with deionized water and ethanol alternately. Next, the film was heated on a hot plate and then incubated in N,N-bis(acryloyl)cysteamine (BACA) / methanol solution (5 mg mL -1 Finally, the AgNW-S was rinsed with methanol to remove excess BACA residues; (3) Preparation of PDA-TCNF / AgNW-S composite electrode: First, the AgNW-S conductive film was transferred to the PDA-TCNF wet film. Then, hot pressing was performed to form a PDA-TCNF / AgNW-S composite electrode. The composite electrode after interface adjustment was named PDA-TCNF / AgNW-S composite electrode. The PDA-TCNF / AgNW-S composite electrode was exposed to ultraviolet light <400nm through a mask, and the light power density and irradiation time were adjusted. The electrode was named PDA-TCNF / AgNW-S / 3 composite electrode.
2. The preparation method according to claim 1, characterized in that: The thickness of the nanocellulose film in step 1) is 0.2-0.3 mm, the diameter of the nanocellulose is 20-40 nm, and the length is 500-2000 nm; The dried TCNF membrane is immersed in a 50 wt % 3-aminopropyltriethoxysilane (APTES) ethanol solution for 15 to 60 minutes, ultrasonically cleaned for 1 hour, and stirred at room temperature for 1 to 4 hours.
3. The preparation method according to claim 1, characterized in that: In step 2), AgNWs dispersion (2 mg mL -1 ) is spin-coated on a glass slide at a spin-coating speed of 800 to 1200 rpm, and the AgNW-S film is heated at 60 to 90° C. for 10 to 40 min; The N,N-bis(acryloyl)cysteamine (BACA) / methanol solution (5 mg mL -1 ) and soak for another 10 to 60 minutes.
4. The preparation method according to claim 1, characterized in that: The step 3) transfers the AgNW-S conductive film onto the PDA-TCNF wet film; then, hot presses at 60-80° C. for 6-12 hours; the optical power density is 30-60 mW cm -2 The irradiation time is 2 to 20 minutes respectively.
5. A nanocellulose-based flexible transparent electrode prepared by the method according to any one of claims 1 to 4.
6. The nanocellulose-based flexible transparent electrode according to claim 5, characterized in that: The contact resistance of the nanocellulose-based flexible transparent electrode is 7.26Ωsq -1 ~108.2Ωsq -1 ; Transmittance (550nm) is 80% to 91%; Quality factor (FoM) is 33.7 to 324.2; The number of times of resisting tape adhesion is 10 to 350 times.
7. The nanocellulose-based flexible transparent electrode according to claim 5 or 6 is applied to a thin film heater.
8. The thin film heater according to claim 7 is manufactured by applying a silver paste brush on both ends of the composite electrode and connecting a constant voltage DC power supply using a conductive copper tape as a channel. The voltage of the DC power supply of the film heater is 1-5V.
9. The thin film heater according to claim 8, characterized in that: The saturation temperature range of the film heater is between 32.1 and 133.7°C.